Efficacy of parenteral formulations of desmopressin in the treatment of bleeding disorders: A systematic review. Issue 213 (May 2022) - Sreeraman, Shreyas; McKinlay, Stuart; Li, Allen; Crowther, Mark; Motalo, Oksana
Abstract: Introduction: Desmopressin (DDAVP) is a proven therapy for bleeding disorders; however, the therapeutic efficacy of different parenteral formulations has never been systematically analyzed. This study investigated whether subcutaneous (SC) DDAVP provides equivalent hemostatic efficacy to intravenous (IV) desmopressin, particularly in patients with mild to moderate bleeding tendencies from hemophilia A (HA) or von Willebrand disease (vWD). Materials and methods: We searched PubMed, EMBASE, MEDLINE, Cochrane, and CINAHL databases for observational studies and randomized controlled trials which compared the hemostatic efficacy of parenteral formulations of DDAVP in healthy patients and those with bleeding disorders. Two reviewers independently performed screening and data extraction. Extracted data included Factor VIII (FVIII) levels, von Willebrand factor (vWF) antigen levels, and vWF activity. Results: The search strategy yielded a total of 5519 studies. Twelve studies met the inclusion criteria and were included in the review. Seven out of eight studies conducted in patients with bleeding disorders and all four studies conducted in healthy subjects found no difference in hemostatic efficacy between parenteral formulations. A meta-analysis was not performed due to disparities between study design and outcomes of interest. Conclusions: Our study showed that IV and SC administration of DDAVP appeared to result in near equivalent hemostatic efficacy; however, the strength of these findings is limited by the small number and lack of comparability in the primary studies. A sizable contemporary study powered to detect differences in coagulation factor levels would be required to confirm our findings. Highlights: Desmopressin is a treatment modality for hemophilia A and von Willebrand disease. Few reviews have compared intravenous and subcutaneous formulations of desmopressin. 11 out of 12 studies show no significant difference between desmopressin formulations. Better quality and more recent evidence is required to make definitive conclusions.